2019
DOI: 10.1002/jcp.28133
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ROS–NF‐κB axis by tuna backbone derived peptide ameliorates inflammation in necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is the most common life‐threatening gastrointestinal disease encountered in the premature infant. It has been shown that the intercellular reactive oxygen species (ROS) generation activated by lipopolysaccharide involved in the nuclear factor kappa B (NF‐κB) activation and pathogenesis of NEC. Here, we report that an antioxidant peptide from tuna backbone protein (APTBP) reduces the inflammatory cytokines transcription and release. APTBP directly scavenges the free radical throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Cheng [22] showed that the small molecular peptides isolated and purified from the enzymatic hydrolysis of tuna boiled juice had great anti-inflammatory activity. Zhang [23] demonstrated that antioxidant peptides extracted from tuna bone protein enhanced the inflammatory response of necrotizing colitis caused by decreasing reactive oxygen species (ROS) and inhibiting the NF-κB pathway. Wang [24] illustrated that enzymatically hydrolyzed peptides from Skipjack (Katsuwonus pelamis) had a good regulating effect on inflammation and intestinal flora of UC model mice induced by DSS.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng [22] showed that the small molecular peptides isolated and purified from the enzymatic hydrolysis of tuna boiled juice had great anti-inflammatory activity. Zhang [23] demonstrated that antioxidant peptides extracted from tuna bone protein enhanced the inflammatory response of necrotizing colitis caused by decreasing reactive oxygen species (ROS) and inhibiting the NF-κB pathway. Wang [24] illustrated that enzymatically hydrolyzed peptides from Skipjack (Katsuwonus pelamis) had a good regulating effect on inflammation and intestinal flora of UC model mice induced by DSS.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing prolyl hydroxylase 2 (PHD2) could also alter the effect of bone marrow mesenchyml stem cells (BM-MSCs) via the NF-κB-dependent mechanism 48 . APTBP, an anti-oxidative peptide, could improve the NEC in ammation by inhibiting ROS-NF-κB axis 49 . In this study, we found that PDTC could ameliorate the in ammation, oxidative stress and intestinal permeability in NEC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of intestinal epithelial cells is linked to NEC progression [ 18 ]. Extrinsic lipopolysaccharide-induced reactive oxygen species accumulation results in NF- κ B activation and subsequent release of proinflammation cytokines, including IL-6 and IL-1 β , which are involved in NEC pathogenesis [ 19 , 20 ]. KEGG pathway analysis identified pathways that are mainly linked to NEC progression.…”
Section: Discussionmentioning
confidence: 99%